Online Classrooms and Ontological Crises Pedagogies of Porosity and Political Participation - Moon, Zachary (2017)
The purpose of this article is to explore the challenges and opportunities in engaging theological education in online classrooms, with particular attention to how these online classrooms can nurture democratic participation and empower political agency. Charles Taylor and others utilize the imagery of "porous" and "buffered" in describing selves and spaces, and this article advocates for disrupting patterns of buffering-practices that seek to dominate and guard against intersubjective influencers-and envisions how more porous learning environments where multiple, co-creative agents of learning as well as contexts and communities are invited into the learning process. Ella Baker, a crucial pedagogue of the Civil Rights Movement, serves as an interlocutor in reimagining political participation in educational and formational spaces.
Keywords: Pedagogy; Activism; online teaching; Pastoral Theology; porous; Theological Education